La financiarisation de l’économie sud-coréenne depuis 1997 : analyse du changement de régime d’accumulation - Pauline Debanes (Revue de la Régulation)
This thesis examines the financialization of the accumulation regime in South Korea since the 1997 Asian crisis based on three inter-related transformations: 1) macroeconomic and institutional changes under the neoliberal restructuring; 2) the growing integration of firms into financial and trade markets; 3) the restructuring of the role of the state under the drive to promote technology-intensive sectors. Building upon regulation theory and post-Keynesian economics, the analysis considers several levels—macroeconomic, institutional and political, and different scales—local, national, transnational. The thesis discusses the determining conduits of financialization and the local characteristics of this global process, conceptualized as intrinsically uneven and hierarchical.